Religious Heterogeneity and Cultural Diffusion: The Impact of Christian Neighbors on Muslim and Druze Women's Participation in the Labor Force in Israel. (August 2015) - Yonay, Yuval P; Yaish, Meir; Kraus, Vered
This study exploits the unique demographic structure of the Arab-Palestinian minority in Israel and their geographical immobility in order to help resolve the riddle why women in the Middle East and North Africa are less likely to participate in the labor force than women elsewhere in the world. We show that, controlling for economic variables, Muslim and Druze Arab women are more likely to enter the labor force if they live in a locality where Christian Arabs live as well. A possible explanation of this finding is the impact of social interaction among people who have different cultural schemas. Female labor force participation is rising throughout the Middle East, including among Arab-Palestinians in Israel, but the tempo of this transformation depends on various local variables, and in this article we identify one such factor, namely, the ethno-religious composition of a community.